MECHANISMS OF AUTOPOIESIS IN THE SYSTEM BASIS MAN-MADE WORLD - Sergey F. Sergeev (Открытое образование (Москва))
The article is devoted to the problem of co-evolution of man-made environment, and human society. We explain the information and network technologies impact both on mankind and society. Our main goal is to show the techno-biology stage of human civilization evolution and present the concept of total human-authopoetic systems. We present the interpretation of autopoietics self-orienting and intersystem interactions arising from man-made environment. We describe the mechanism of environmental systems dynamics which organizes the development of global man-made environment and human health.